THE TRANSLATION STRATEGY OF IDIOMATIC EXPRESSIONS IN THE INTERN FILM SUBTITLE - Pauline M Charita; Gratiana Sama; Yuliana M D K Kara; Marianus Roni (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2026)
This study aims to examine the translation strategies of idiomatic expressions in the subtitles of the film The Intern using Baker's (1992) theory of idiomatic expression translation strategies, which includes four strategies: using idioms with the same meaning and form, using idioms with the same meaning but different forms, translating through paraphrasing, and translating through omission. The research method used was descriptive qualitative with data sources in the form of English subtitles and their Indonesian translations. From 25 idiom data, three strategies were found to be used: the use of idioms with the same meaning and form (4 data), the use of idioms with the same meaning but different forms (9 data), and translation through paraphrasing (12 data). The omission strategy was not found. The results of the study show that the paraphrasing strategy is the most dominant because it is considered more flexible in adjusting to the target language context. Further research is expected to analyze different objects and consider aspects of procedure and translation quality.